Health care systems in liberal democracies - Wall, Ann (Ann L.) (Routledge, 1996)
Ann Wall explores the continuing quest for solutions to apparently intractable problems, examining the ways in which health care is organized and delivered in Australia, Italy, the Netherlands, Sweden, the UK and the US.